2010
DOI: 10.1007/s11664-010-1124-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Treatment on the Luminescence of ZnO

Abstract: The effects of chemical treatment on the luminescence of ZnO were investigated by cathodoluminescence. For this purpose, ZnO ceramics and O-and Zn-terminated faces of ZnO single crystals were studied. The samples were dipped in KOH and HCl solutions as well as pure H 2 O for 3 min. H 2 O and HCl treatments of ZnO ceramics can increase or decrease the initial ultraviolet (UV) intensity depending on the location examined, and induce an increase of the UV intensity under e-beam irradiation. HCl treatment of the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Figures 12(b) and (c) show the respective CL images of the O-and Zn-faces irradiated for 3600 s. The luminescence is weaker in the irradiated than in the unirradiated area for the O-face, but it is stronger for the Zn-face. This experiment suggests that the surface plays an important role in the variation of the intensity during CL measurements [71].…”
Section: Variation Of the CL Intensity During The Measurementsmentioning
confidence: 71%
See 2 more Smart Citations
“…Figures 12(b) and (c) show the respective CL images of the O-and Zn-faces irradiated for 3600 s. The luminescence is weaker in the irradiated than in the unirradiated area for the O-face, but it is stronger for the Zn-face. This experiment suggests that the surface plays an important role in the variation of the intensity during CL measurements [71].…”
Section: Variation Of the CL Intensity During The Measurementsmentioning
confidence: 71%
“…We have observed a significant degradation of the CL intensity in ZnO [21,22,70,71]. Figure 12(a) shows the CL spectra of a bulk ZnO polycrystal and nanorod-structured ZnO tetrapods, after 20 and 3600 s of irradiation at 5 kV.…”
Section: Variation Of the CL Intensity During The Measurementsmentioning
confidence: 96%
See 1 more Smart Citation
“…Dierre et al studied the CL of the O-face and Zn-face of ZnO crystal under electron beam irradiation and found that the enhancement effect at the initial stage was only observed on the Zn-face sample, which suggests the UV enhancement is indeed due to the desorption of negative ions (e.g. O 2− and OH − ) from the surface [27,28]. For a higher accelerating voltage of 10 kV, the UV emission intensity decreases with electron beam exposure time, which is likely caused by the dissociation of hydrogen bound in oxygen vacancies [27].…”
Section: Resultsmentioning
confidence: 99%
“…The desorption of the hydroxyl groups ͑13.0 s͒, which can affect the surface band bending, 18,[44][45][46] may cause the increase in the UV intensity at the Zn-face. 47 It is intriguing that the O + peak at 14.2 s TOF is observed for the clean O-face but not the clean Zn-face ͑Fig. 2͒, and that it increases for the unclean O-face while it decreases for the unclean Zn-face for 1.5 keV irradiation ͑Fig.…”
Section: Discussionmentioning
confidence: 99%